Alveolar Bone Repair Dynamics in Rats Influenced by Coffee Ingestion: A Confocal Microscopy Analysis - dos Santos, Kaio; Freire, Alexandre R; Ferreira-Pileggi, Beatriz C; de Freitas, Isabella Andreazza [UNESP]; Okamoto, Roberta; Prado, Felippe B; Rossi, Ana Cláudia (Springer Nature, 2025)
After surgical tooth extraction, it is necessary to maintain the environment of the oral cavity in appropriate conditions to favor alveolar bone repair. Coffee includes multiple bioactive compounds; some of these compounds can affect bone metabolism. The aim of this study was to investigate the effect of coffee ingestion on alveolar bone dynamics after tooth extraction using confocal laser microscopy. Eight male Wistar rats, aged two months, were used and divided into two groups: the control group, in which the normal diet was maintained, and the experimental group, with coffee ingestion. In both groups, extraction of the upper right incisor was performed. The fluorochromes calcein was injected at 14 days and alizarin at 28 days in rats. The sample was euthanized 28 days after the tooth extraction. The right maxilla was removed, processed, and analyzed under a confocal laser microscope, and the mineral apposition rate and the alveolar bone area marked with calcein and alizarin were obtained. There was no statistically significant difference between groups for bone mineralization rate. The two-way ANOVA compared differences between groups and fluorochromes; the interaction between the groups was not statistically significant. The intragroup analysis showed a statistically significant difference between the fluorochromes injected at 14 days and 28 days after tooth extraction. There was a tendency for there to be a decrease in renewed bone in the group that drank coffee, although this was not significant.